Smart Body Temperature Monitoring Berbasis IoT dengan Integrasi Kamera Smartphone - Senna Hendrian; V. H. Valentino; Wisdariah Wisdariah; Danang sutrisno; Nico Bustanul Anshary (Neptunus: Jurnal Ilmu Komputer Dan Teknologi Informasi, 2026)
The development of Internet of Things (IoT) technology has encouraged innovation in the healthcare sector, particularly in monitoring human body temperature in real time. Body temperature monitoring is important as an early indicator of health conditions. This study aims to design and implement a Smart Body Temperature Monitoring system based on IoT integrated with a smartphone camera for user monitoring and identification. The system utilizes an ESP32 microcontroller, MLX90614 temperature sensor, and smartphone integration to display monitoring results in real time through an IoT dashboard. The research method used is the Waterfall method consisting of requirements analysis, system design, implementation, testing, and maintenance. The results show that the developed system is capable of monitoring body temperature accurately and transmitting data in real time via internet connection. The integration of smartphone cameras also improves user monitoring effectiveness and supports digital healthcare systems. Based on system testing, the application operates properly and can support body temperature monitoring activities efficiently.